Uveal melanoma following Bruton's tyrosine inhibitor use for the treatment of hematologic malignancies - Tara Murty; Jonathan H. Lin; Prithvi Mruthyunjaya (American Journal of Ophthalmology Case Reports)
Purpose: To report two new cases and summarize one case of uveal melanoma following treatment of hematologic malignancies with Bruton's tyrosine kinase inhibitors. Observations: A 71-year-old male, with a history of Waldenstrom macroglobulinemia treated with an anti-CD20 antibody and BTKi, was diagnosed with a choroidal melanoma with intraocular metastasis. A 73-year-old female, with a history of Mantle Cell Lymphoma treated with an alkylating chemotherapy and an anti-CD20 antibody, relapse, and subsequent treatment with BTKi, was diagnosed with a uveal melanoma. Conclusions and Importance: Patients being treated with BTK inhibitors may be at higher risk for the development of uveal melanoma. Based on our findings, we recommend increased surveillance of this patient population for secondary primary or metastatic uveal melanoma. Continued documentation of occurrence in conjunction with research at a molecular and cellular level are warranted to better understand the impact of systemic cancer therapies on secondary malignancies.